Simulation study on the size effect of joint roughness on bulk modulus - Liang, Wenxu; Li, Yu; Wang, Jie; Hu, Gaojian; Fu, Wei; Sun, Lei (Frontiers in Materials, 2023)
The bulk modulus reflects the deformation of rock macroscopically and plays a vital role in geological exploration, oilfield development, and drilling. The bulk modulus not only changes under different rock sizes, but also varies with joint roughness. Therefore, it is very important to accurately estimate the bulk modulus of rough jointed rock and evaluate its deformation. In this paper, the influence of joint roughness and rock size on bulk modulus was discussed by regression analysis of 25 sets of simulation models. The research shows that with the increase of rock size, the bulk modulus decreases exponentially, and with the rise of joint roughness, the bulk modulus increases as a power function. With the rise of joint roughness, the characteristic size of bulk modulus increases exponentially, and the characteristic bulk modulus increases as a power function. The paper gives the specific forms of these relations.